Vivências de estagiários de licenciaturas e contextos emergentes na educação básica - Trindade, Thais Pulgatti (2019)
This study inserts itself in the research line of Formation, Knowledges and Professional Development, of the postgraduate program in Education from the Federal University of Santa Maia (UFSM). This study aims to comprehend how three graduation courses interns constitute themselves as teachers from the experiences with basic school students and their contexts. The main theorists that contributes with the reflections within this research into scope of teacher formation are: Bolzan (2001, 2006, 2008), Bolzan and Isaia (2006), Isaia and Bolzan (2006, 2007a, 2007b, 2008, 2009, 2010, 2018), Isaia, Bolzan and Maciel (2011), Isaia (2003a, 2003b), Marcelo Garcia (1999), Morosini (2006), Diniz Pereira (2007), Fiorentini (2008), Mizukami (2002), Sarmento (1994), Zabalza (2004), and others. With regards to emerging contexts we utilized: Bolzan (2016), Morosini (2006, 2014), Libâneo (2002), RIES (2009,2013), Dalla Corte (2017), Kenski (2013). To discuss the internship Pimenta e Lima (2004, 2011) was used. The study is characterized as a qualitative research developed from a sociocultural narrative approach built by Bolzan (2001, 2006), starting from the studies of Vygotski (1993, 1994, 1995), Bauer and Gaskell (2002), Clandinin and Conelly (2011), Flick (2004, 2009), Minayo (2009) and Denzin (2005). For data collection, narrative interviews had been utilized, starting with guided topics directed to basic school students learning. The descriptive interpretative process of the findings were based on the students narratives, to what permitted the construction of a big category: Formative course, which is constituted by three dimensions, the learning of teaching: the teacher’s self build up, supervised internships as a initial formation space and basic education and emerging contexts. Those dimensions where organized from many categorical elements. In that sense, it became evident during the study that the internships comprehend these emerging contexts being everyday school's challenges. Into their narratives they express the difficulties encountered through the supervised internship, highlighting the state schools infrastructure precariousness and lack of materials. Inclusion also is manifested by the subjects, when they report the teacher's and management unpreparedness to handle the inclusion in the context, indicating that a "false inclusion" exists within the educational institutions. Also, the interns recognize the importance of the formative spaces offered by the University for the learning of teaching. They express the need to have a curricular reorganization in the teacher formation courses that make it possible a greater participation of students in the formative spaces with extra-curricular experiences. The interns also manifest the necessity of a higher involvement from the teachers/advisors in the school context. The accomplished study and the findings discussions allow understanding a little more what the intern’s conceptions about the emerging contexts are and how this theme is problematized within the initial formation courses and how does the formation of those subjects happen from what is offered by the university.